THE EFFECT OF GIVING CUCUMBER (Cucumis sativus) TO DECREASE HEMOGLOBIN TROMBOSITE AND IMPROVEMEN IN PRE-ECLAMMED PATIENTS AT DEWI SARTIKA HOSPITAL: Cucumber to decrease hemoglobin - Sarmiati, Novia; Deden Miftah, Erwin Azizi Jayadipraja; La Banudi (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2020)
Background: According to the World Health Organization (WHO) every day in 2015, around 830 women die from complications during pregnancy and child birth. Globally, maternal mortality in the world was 303,000 in 2015. The maternal mortality rate (MMR) in Indonesia based on the Indonesian Health Demographic Survey (IDHS) in 2012 was around 359 / 100,000 live births, this figure increased compared to 2007, which was around 228 / 100,000 live births. Based on Dewi Sartika General Hospital’s data with preeclampsia cases for the last three years. In 2017, the number of births in 1855 who experienced preeclampsia were 305 cases. In 2018, the number of births in 1822 who experienced preeclampsia was 334 cases. In 2019, the number of deliveries in 2007 who experienced preeclampsia was 377 cases. For 2020 January to June number of deliveries695 the incidence of preeclampsia was 164 cases. Methods: This study used a quasi-experimental method with a pre-test-post-test control group design. The population in this study was 164 preeclampsia patients from August to October 2020. Result: The wilcoxon test showed p value was 0.0000 < ? = 0.05 on decreased hemoglobin and increased platelets Conclusion:There was an effect of cucumber on decreasing hemoglobin and increasing platelets in pre-eclampsia patients at DewiSartika General Hospital.